Factors Affecting the Resilience of Adolescent Victims of Cyberbullying in Dual-Earner Families - Rizkillah, Risda; Aldera, Wydelia Rahmanisa (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Adolescents are the age group that uses social media the most and is the age group most vulnerable to becoming perpetrators or victims of cyberbullying. This research generally aims to analyze differences based on region, relationship, and the influence of parent-adolescent interactions and coping strategies on adolescent resilience. This research uses a quantitative approach and cross-sectional study design using survey and questionnaire methods. Sampling was carried out using purposive sampling with a total sample of 98 adolescents. This research was located in Bogor Regency and City, West Java. The results of the independent t-test showed that there are significant differences in adolescent resilience based on region. The results of the correlation test show that adolescent age has a significant negative correlation with the dimensions of self-acceptance. Family size has a negative correlation with parent-adolescent interactions. Correlation test results show that parent-adolescent interaction and coping strategies significantly correlate with adolescent resilience. The results of regression tests show that region, mother's education, parent-adolescent interactions, and coping strategies significantly positively affect adolescent resilience. The parents-adolescent interaction, coping strategies, and resilience in adolescents in this study are mostly still in the moderate category, so they still need to be improved.